DAUR ULANG AIR LIMBAH DOMESTIK KAPASITAS 0,9 M3 PER JAM MENGGUNAKAN KOMBINASI REAKTOR BIOFILTER ANAEROB AEROB DAN PENGOLAHAHAN LANJUTAN - Widayat, Wahyu (Center for Environmental Technology, 2009)
Water pollution in the big cities in Indonesia, especially in DKI Jakarta has shown serious problems. One of the potential sources of water pollution is domestic wastewater that is wastewater from kitchens, laundry, bathing and toilets. These problems have become more serious since the spreads of sewerage systems are still low, so that domestic, institutional and commercial wastewater cause severe water pollution in many rivers or shallow ground water. There are a number of ways to converse water resources, one of them is to treat domestic waste water by communal system and then it is continued by advance process for recycling of wastewater. In this paper, it will be discussed recycling of domestic wastewater by communal system that combine the biological system using anaerobic-aerobic biofilter reactor for removing organic pollutant in wastewater and the advance process consisting of oxidation process, filtration by manganese zeolite filter, filtration byÃ‚Â rapid sand filter, filtration by carbon filter and desinfection by ultraviolet sterilisator. The sterilisator is improve quality of tread wastewater being clear Ã‚Â water as an alternative for water use save.Ã‚Â Key wrods : Limbah, domestik, daur ulang, biofilter, pengolahan lanjutanÃ‚Â